VD_FINDINFO HC / 2014 / 931 vom 18. November 2014 - VD Tribunal cantonal (2014)
DROIT D'OBTENIR UNE DÉCISION, RADIATION DU RÔLE, PROCÈS DEVENU SANS OBJET, DÉPENS | 106 al. 1 CPC (CH), 242 CPC (CH), 319 let. c CPC (CH)